2022
DOI: 10.31219/osf.io/m6yvb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trading Liberties: Most citizens do support restricting freedoms in times of crisis

Abstract: Major crises regularly lead to a public debate about whether the government should be able to restrict personal freedoms in the interest of public welfare. Using a factorial survey experiment administered to more than 10,000 online survey respondents in Germany during the COVID crisis, we assess under what conditions citizens are willing to sacrifice individual civil freedoms in the interest of public well-being. Despite highly visible protests against Covid policies, we document broad willingness to accept re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…When it comes to voters, a case likely can be made that different individuals, in terms of, say, personal traits or political preferences, react in different ways to specific limitations (Collis et al, 2022). While research has shown the presence of generalized effectse.g., lockdowns enforced during the pandemic increased trust in democracy and government across Europe in the shortterm (Bol et al, 2021), and a large majority of citizens support the limitation of individual freedoms during crisespatterns of approval can indeed differ greatly across subgroup categories (Hartmann et al, 2022). For instance, Terry et al (2020) report that younger individuals were more likely to showcase a negative mood toward the pandemic at the beginning of the crisis, Auton and Sturman (2022) demonstrate that greater compliance with COVID-19 restrictions was more likely among more informed respondents, and Modersitzki and colleagues (2021) show that respondents high in extraversion and neuroticism were more likely to perceive measures as more restrictive.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to voters, a case likely can be made that different individuals, in terms of, say, personal traits or political preferences, react in different ways to specific limitations (Collis et al, 2022). While research has shown the presence of generalized effectse.g., lockdowns enforced during the pandemic increased trust in democracy and government across Europe in the shortterm (Bol et al, 2021), and a large majority of citizens support the limitation of individual freedoms during crisespatterns of approval can indeed differ greatly across subgroup categories (Hartmann et al, 2022). For instance, Terry et al (2020) report that younger individuals were more likely to showcase a negative mood toward the pandemic at the beginning of the crisis, Auton and Sturman (2022) demonstrate that greater compliance with COVID-19 restrictions was more likely among more informed respondents, and Modersitzki and colleagues (2021) show that respondents high in extraversion and neuroticism were more likely to perceive measures as more restrictive.…”
Section: Introductionmentioning
confidence: 99%